Escritores de uma terra sem face: o ensino e produção de poesia sobre o município de Abaetetuba - FREITAS, Camilla Dias de (2019)
This study resulted from an intervention project entitled "WRITERS OF A LAND WITHOUT FACE: the teaching and production of poetry about the municipality of Abaetetuba", whose main objective was to organize a didactic sequence for the teaching of the lyrical genre and through that publish a booklet of free verse poetry written by high school students in which they should make use of objects, people, places, events, food and other situations belonging to the culture of Abaetetuba, providing the lyrical face to the municipality according to their previous knowledge and acquired after the intervention and still making this composition a way to exercise their roles as citizens demonstrating the face that the municipality presents for these students. It was carried out a survey of information and the application of the didactic sequence in a state public school of Abaetetuba: School Bernardino Pereira de Barros, that had as subjects of the intervention the students of the 2nd stage of the modality of Education of Young People and Adults (EJA). The knowledge about liric genre was in the light of the studies of Luciano Marcos Dias Cavalcanti (2014). However, the relevance of the work is justified by the guidelines of the National Curriculum Parameters of Portuguese Language of the high school (2000) and Curricular guidelines for high school (2006). In addition, the didactic sequence is appreciated according to Joaquim Dolz and Bernand Schneuwly (2004) and Alda Beraldo (1989 and 1990). It is understood that the lyrical composition is of utmost importance in the Portuguese Language classes for the construction of the subject as a means of education of the sensibility, which is the search for a knowledge as great and important as the scientific, that is, the humanization of the men.